To glove or not to glove? Investigations into the potential contamination from handling of paper-based cultural heritage through forensic fingerprinting approaches - van der Pal, Karin J.; Popelka-Filcoff, R.S.; Smith, G.D.; Van Bronswijk, Bill; Lewis, Simon (2021)
The handling of cultural heritage objects has become a highly debated topic in the last decade. The work and outcomes described in this paper are aimed to provide objective data to assist in making appropriate decisions as to whether or not wearing gloves is appropriate in a given situation. The forensic fingermark development techniques of 1,2-indandione and single metal deposition II were used to investigate the efficacy of handwashing and glove use to improve the information available when deciding whether to use gloves when handling paper objects. It was found that fingermarks did not permeate through polymer glove types but could through cotton gloves. It was also shown that the amounts of observable fingermark residues were greater 5 min after handwashing than if handwashing had not occurred, undermining previous arguments for not wearing gloves if hands could be washed before object handling.